Inheritance Rights of The Death Benefit Under The Social Insurance Employment Agency - Yasim, Sulastri; Novitasari, Ika; Sulaeman; Amaliah, Rezki (Alauddin Law Development Journal (ALDEV), 2024)
The urgency that the BPJS Employment program is held with the aim of providing death benefits to the heirs and benefits so that the heirs can meet the basic needs of a decent life when the participant dies. This research is a normative legal. The results showed that in the provision of death benefits to the heirs must have the status of a spouse (widow or widower) or child of the participant. If the spouse or child does not exist, the heirs are blood descendants in a straight line up and down to the second degree or siblings or in-laws or parties designated in the will by the participant. This is in line with the inheritance system according to the Civil Code, where there are two ways to obtain inheritance, namely first, obtaining inheritance based on the provisions of the law and second, obtaining inheritance based on the will.